Pengaruh Tangibles, Reliability, Dan Responsiveness Terhadap Pembelajaran Online Pada Masa Pandemi Covid-19 (Studi Kasus Pada Mahasiswa/I Fakultas Ekonomi Dan Bisnis Universitas Muhammadiayah Metro) - Bhaswara, Ilham Prima; Nasikah, Durotun (Universitas Muhammadiyah Metro, 2023)
ABSTRACT The current COVID-19 virus in Indonesia has an impact on the entire community. According to kompas, March 28, 2020, the impact of the COVID-19 virus occurred in various fields such as social, economic, tourism and education. Circular (SE) issued by the government on March 18, 2020, all indoor and outdoor activities in all sectors are temporarily postponed in order to reduce the spread of corona, especially in the education sector. This study aims (1) To determine whether Tangibles affect student satisfaction (2) To determine whether Reliability affects student satisfaction (3) To determine whether Responsiveness affects student satisfaction (4) To determine whether Tangibles, Reliability and Responsiveness together the same effect on student satisfaction. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. The population in this study was taken based on the class of 2018 which amounted to 257 students. The criteria in this study were students majoring in Management and accounting in 2018. The results showed that (1) there was a positive influence of Tangibless on student satisfaction (2) there was a positive influence of Reliability on student satisfaction (3) there was a positive influence of Responsiveness on student satisfaction (4) there was a positive influence of Tangibless, Reliability and Responsiveness on customer satisfaction. Keywords: Tangibles, Reliability, Responsiveness and Customer Satisfaction